Social support and subjective well-being among undergraduate students in School of Health Sciences Universiti Sains Malaysia - Arifin, Nur Shahidah (Universiti Sains Malaysia, 2023)
Life in university is a steppingstone and a new challenge for student in learning process. University is a place where students are started to be independent, learning new things and being introduced with various academic syllabus, university activities and curriculum that differs from school. Learning system in university are much complex and packed causing students’ mental health easily disturbed. Social support is vital to ensure a person have an individual or group which they trust and rely on, consist of family, friends or significant others. The general objective of this study is to assess the social support and subjective well-being among undergraduate students in School of Health Sciences USM. A cross-sectional study was conducted involved 333 participants using self-administered questionnaire. The data were analyzed using descriptive statistics and Chi Square test using Statistical Package Social Science (SPSS) version 26.0. Majority of students have high level of social support 184 (%55.3), 140 (42%) recorded moderate social support meanwhile only 9 (2.7%) recorded low social support. The mean value for subjective well-being is (mean= 4.67, SD= 1.478). Chi Square revealed that there is significant association between social support and subjective well-being (p<0.001). In summary, the result of this study showed that social support has an impact towards subjective well-being since it is importance for the formation of student to overcome challenges and psychological and behavioral problems in university.